Fraud Triangle Perspective on Financial Statement Fraud with Quality Audit as a Moderating Variable - Hudin, Emilio; Widagdo, Bambang; Jihadi, Muhammad (University of Muhammadiyah Malang, 2024)
Financial Statement Fraud is a significant problem in the financial sector, where companies deliberately misrepresent their financial information to deceive stakeholders. Therefore, this study aims to analyze the perspective of Financial Stability, Financial Targets, and External Pressure on Financial Statement Fraud with Quality Audit as a moderating variable. The population in this study is all companies in the Primary Consumer Goods sector, which numbered 87. After the normality test, the samples used were 60 companies. Based on the regression test results, three variables have no significance on fraud's financial statement. The auditor quality variable does not moderate the relationship between financial stability, financial targets, and external pressure to financial statement fraud. Although financial stability, financial targets, and external pressure do not directly affect financial statement fraud, companies can prioritize financial risk management by focusing more on other aspects that may significantly impact financial statement fraud.